Legislative history analysis of the operation of foreign higher education institutions in Hungary - Bárány, Viktória Fanny (Pécs journal of international and European law, 2018)
The legislative changes to the higher education institutions operating in Hungary that entered into force in April 2017 generated a serious policy/political debate both in the public and among politicians and professionals involved in the topic. The goal of my paper is to examine and analyze – both the previous and the current – respective regulation, furthermore to present and evaluate the impact of the changes and modifications from socio-economic and scientific aspects. I present the forms of operation of foreign higher education institutions operating in Hungary under the current regulations and draw my conclusions.